Effect of Ginger Extract on Gentamycin Induced Testicular Atrophy in Albino Mice - Bukhari, Anila Shah (International Journal of Pathology, 2022)
Background: Gentamicin is a broad spectrum antibiotic used in wide range of infective diseases including infertility cases of high leukocyte count in semen. Its therapeutic applications are however hampered due to its nephrotoxicity and ototoxicity. It is known to cause testicular damage and may lead to infertility. It has been claimed that Ginger Extract restores sperm motility and fertility in case of gentamicin induced testicular toxicity. Objective: To assess the preventive effect of Ginger Extract on gentamicin induced testicular toxicity Methods: 50 adult albino male mice were selected and divided into following groups; Group A: control group. Group B: Only intraperitoneal gentamicin with no Ginger extract, Group C1: 25 mg/kg intraperitoneal gentamicin with oral 100 ml/kg Ginger extract, Group C2: 25 mg/kg intraperitoneal gentamicin with intraperitoneal 100ml/kg Ginger extract, Group D1: 50 mg/kg intraperitoneal gentamicin with oral 100 ml/kg Ginger extract, Group D2: 50 mg/kg intraperitoneal gentamicin with intraperitoneal 100ml/kg Ginger extract. All albino mice were sacrificed after 2 weeks. Testes were preserved in formalin; histological slides were prepared and examined under light microscope. Data was recorded on a Performa and analyzed by SPSS version 20 and t-test was applied for weights of mice and testes. Results: Group A, C and D showed normal testicular morphology while Group B showed decreased diameter of seminiferous tubules, congestion of blood vessels, necrosis, occasional apoptosis, reduced sperm counts and distorted tunica albuginea with a p value of <0.001confirming protective and reversal effects of experimental work. Conclusion: Ginger extract has protective effects on gentamicin induced testicular toxicity in albino mice